Effects of biostimulation by sugarcane bagasse and coffee grounds on sewage sludges, focusing agricultural use: Microbial characterization, respirometric assessment and toxicity reduction - Mazzeo, Dânia Elisa Christofoletti [UNESP]; Misovic, Andrea; Oliveira, Flávio Andrade; Levy, Carlos Emílio; Oehlmann, Jörg; de Marchi, Mary Rosa Rodrigues [UNESP] (Elsevier, 2020)
Sewage sludge (SS) exhibits a relevant agronomic potential due to the high content of organic matter and nutrients. However, the presence of several toxic substances can prevent its agricultural application. This study evaluated if the incorporation of stimulating agents (coffee grounds and sugarcane bagasse) could contribute to an effective increase of the SS biodegradability in order to decrease its toxicity. The samples were prepared mixing aerobic or anaerobic sludge with soil, soil and bagasse, and soil and coffee grounds. Respirometric tests showed that stimulating agents enhanced the CO2 production. However, in terms of biodegradation efficiency, more satisfactory results were verified for the anaerobic SS, especially when mixed with coffee grounds. The biodegradation also favored the SS sanitization, eliminating the Enterobacteria. For baseline toxicity (Microtox with Aliivibrio fischeri) and phytotoxicity (Lactuca sativa), all the initial samples showed higher effects. Nevertheless, after the biodegradation, this toxicity was significantly decreased and the best results were obtained for the mixtures containing only soil and sludge. For the AREc32 assay (NRF2 mediated oxidative stress response), although a very weak response was observed, this effect was attenuated for the aerobic SS or completely eliminated for the anaerobic SS after the biodegradation. Thus, even though the use of biostimulation agents during the biodegradation led to an enhancement of microbial respiration, their incorporation to the samples do not seem to interfere in the decrease of the toxic potential of the studied SSs. However, the SS biodegradation in aerobiosis was crucial for toxicity reduction and to accelerate its maturity.
Keywords: Enterobacteria; Microtox; Oxidative stress; Phytotoxicity; Sludge stabilization; Solid waste